Robot follow-up vision system for remote intelligent inspection - YANG SONGKAI; CHEN DONGNI; LIU SHENGYI; LIU KAIMING; ZAN YUXING; WEI YUQIAO (2025)
The utility model discloses a robot follow-up vision system for remote intelligent inspection. Comprising head-mounted FPV glasses, transmitting antennas A and B, receiving antennas A, B and C, gyroscope sensors A and B, a control handle, a control button, terminal equipment, an interface converter, a frame, a motor, wheels, a control circuit board, a communication module, a driving circuit board, a two-degree-of-freedom steering engine and a wireless image transmission camera. Wherein the head-mounted FPV glasses are provided with a receiving antenna A, and gyroscope sensors A and B are arranged on the top and the side surfaces of the head-mounted FPV glasses; the control handle is provided with a control button and a transmitting antenna A; the terminal equipment is provided with an interface converter and a receiving antenna B; a motor is arranged on the inner side of the frame; a control circuit board, a driving circuit board and a two-degree-of-freedom steering engine are arranged at the top end of the f